Reverence for Life and Ecological Conversion - Rogers, Chandler D. ca. 20./21. Jh. (Worldviews, 2023)
Friedrich Nietzsche and Albert Schweitzer end up defending radically similar, yet critically opposed conclusions about the human animal and its place in nature, particularly with regard to the ethical awareness that does or does not follow from this situatedness. Arthur Schopenhauer’s notion of the will accounts for their similar foundational assumptions. But what accounts for the fact that their shared desire to affirm the will to life leads to fundamentally opposed ethical conclusions? What keeps Schweitzer’s ascetic ethic of reverence for life from evolving into Nietzsche’s anti-ascetic vision of a second innocence beyond good and evil? We argue that situating the notion of reverence for life within an environmental virtue ethics, as one environmental virtue among many, aiming at ecological conversion, better articulates and motivates the disposition demanded by the ethics of reverence for life.